Pengaruh Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Konsumen Di Aplikasi Shopee Pada Mahasiswa STIE IBMT Surabaya - Rumayomi, Stevania; Iswati, Iswati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The focus of this study is to determine how price and service quality affect consumer product purchasing decisions. In this study, 70 respondents were interviewed using an online questionnaire to collect data. This research uses quantitative research methods, namely research methods related to numbers that are analyzed using statistics. The data collection method uses population, and the sample is collected through distributing questionnaires or questionnaires to correspondents. The results showed that price and service quality have a significant influence on purchasing decisions. Lower prices and better service quality increase purchasing decisions. However, the results also show that the interaction between price and service quality has a greater influence on purchasing decisions. On the other hand, the study also shows that price and service quality can affect the buyer's ability to choose the right product and save time and money. Meanwhile, to support this research, researchers distributed questionnaires via google form. The population in this study were STIE IBMT Class of 2020 students, the sample taken was 70 respondents from the population, so the technique used was a simple random sample. The results showed that price and service quality have a significant impact on consumer purchasing decisions, as indicated by the high value of brand image, customer satisfaction, and trust in the products and services offered. On the other hand, online marketing strategies can influence buyers' ability to choose the right product and save time and money. This research serves as a basis for e-commerce companies to improve effective and efficient online marketing strategies.